2013
DOI: 10.1096/fj.13-229740
|View full text |Cite
|
Sign up to set email alerts
|

Periostin promotes the generation of fibrous membranes in proliferative vitreoretinopathy

Abstract: Proliferative vitreoretinopathy (PVR) is a severe, vision-threatening disorder characterized by the fibrous membrane formation that leads to tractional retinal detachment. There has been no effective therapeutic approach other than vitreoretinal surgery. In this study, DNA microarray analysis of the fibrous membranes revealed significant up-regulation of periostin. We also found increased periostin expression in the vitreous and retinal pigment epithelial (RPE) cells from fibrous membranes of PVR patients. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 48 publications
3
50
0
Order By: Relevance
“…We recently reported an increased expression of periostin in the vitreous and ERMs obtained from patients with PDR and proliferative vitreoretinopathy 14 22 23. In the present study, we showed a higher correlation between the vitreous levels of M-CSF, sCD163 and periostin in eyes with PDR.…”
Section: Discussionsupporting
confidence: 68%
“…We recently reported an increased expression of periostin in the vitreous and ERMs obtained from patients with PDR and proliferative vitreoretinopathy 14 22 23. In the present study, we showed a higher correlation between the vitreous levels of M-CSF, sCD163 and periostin in eyes with PDR.…”
Section: Discussionsupporting
confidence: 68%
“…Periostin has been shown to induce proliferation by activating phosphatidylinositol 3-kinase (PI3K)-dependent pathways (18,32). LY294002, an inhibitor that competes with the ATP binding site in the catalytic domain of PI3K, significantly decreased HTS fibroblast proliferation both in the presence and absence of matrix-associated periostin (P < 0.05, data not shown).…”
Section: Resultsmentioning
confidence: 98%
“…27 Briefly, 5 Â 10 4 cells were seeded in each well and transfected with or without siRNAs. After 1 hour of pretreatment with Dulbecco's modified Eagle's medium with 3% fetal bovine serum containing recombinant TGF-b2 with 5 mmol/L aphidicolin (Sigma-Aldrich) to inhibit cell division, the stoppers were removed to allow cells to migrate into the detection zone.…”
Section: Cell Migration Assaymentioning
confidence: 99%